Managerial Accounting / International Edition: Second Edition - Hilton Ronald W (Mcgraw Hill, Inc, 1994)
Preface, Fundamentals and Cost Accumulation Systems, Managerial Accounting: An Overview, Basic Cost Terms and Concepts, Job-Order Costing Systems, Process Costing and Hybrid Product-Costing Systems, Cost Management Systems for the New Manufacturing Environment, Planning and Control Systems, Cost Behavior and Estimation, Cost-Volume Profit Analysis, Budgeting: Profit Planning and Control Systems, Standard Costing and Performance Measures for the New Manufacturing Environment, Flexible Budgets and Control of Overhead Costs, Responsibility Accounting and Income Reporting, Investment Centers and Transfer Pricing, Using Accounting Information in Making Decisions, Decision Making: Relevant Costs and Benefits, Cost Analysis and Pricing Decisions, Capital Expenditure Decisions: An Introduction, Further Aspects of Capital Expenditure Decisions, Selected Topics for Further Study, Cost Allocation: A Closer Look, Analyzing Financial Statements, Preparing the Statement of Cash Flows, Index.
Preface, Fundamentals and Cost Accumulation Systems, Managerial Accounting: An Overview, Basic Cost Terms and Concepts, Job-Order Costing Systems, Process Costing and Hybrid Product-Costing Systems, Cost Management Systems for the New Manufacturing Environment, Planning and Control Systems, Cost Behavior and Estimation, Cost-Volume Profit Analysis, Budgeting: Profit Planning and Control Systems, Standard Costing and Performance Measures for the New Manufacturing Environment, Flexible Budgets and Control of Overhead Costs, Responsibility Accounting and Income Reporting, Investment Centers and Transfer Pricing, Using Accounting Information in Making Decisions, Decision Making: Relevant Costs and Benefits, Cost Analysis and Pricing Decisions, Capital Expenditure Decisions: An Introduction, Further Aspects of Capital Expenditure Decisions, Selected Topics for Further Study, Cost Allocation: A Closer Look, Analyzing Financial Statements, Preparing the Statement of Cash Flows, Index.